Pengaruh Model Pembelajaran Berbasis Proyek (PBP) Terhadap Hasil Belajar pada Materi Menulis Teks Editorial - Irsan Vanni; Desi Sukenti (UIR Press, 2023)
The learning model affects student learning outcomes seen from the ability of students who do not understand the material to write editorial texts because the teacher uses the conventional model. Researchers are interested in examining learning outcomes using a project-based learning model. (PBP). The problems studied were (1)